VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2018)
Number of pages: 10

VEQ's Summer 2018 Newsletter - Voice of English-speaking Quebec (VEQ) (2018)
Number of pages: 10

Demographic Profile of the English-speaking Communities in the Administrative Region of Capitale-Nationale & MRC La Côte-de-Beaupré - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Capitale-Nationale & MRC La Jacques-Cartier - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Capitale-Nationale & MRC Portneuf - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Capitale-Nationale & MRC Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

VEQ's Spring 2018 Newsletter - Voice of English-speaking Quebec (VEQ) (2018)
Number of pages: 10

Chit Chat Club : Improve Your Second Language Skills While Lending a Helping Hand - Centre Wellness (2018)

Adaptation Initiative Project Guide 2014-2018 - Community Health and Social Services Network (CHSSN) (2018)
The CHSSN’s initiative to adapt health and social services is supported by an investment from Health Canada, through the Roadmap for Canada's Official Languages 2013–2018: Education, Immigration, Communities. This initiative is being undertaken in partnership with the Ministère de la Santé et des Services sociaux (MSSS). An implementation agreement between CHSSN and the MSSS was concluded in order to incorporate the projects into Quebec’s initiatives to improve access to health and social services in English. The agreement also divided the roles and responsibilities among the CHSSN, the MSSS, and the health and social services agencies.

Adaptation Initiative Project Guide 2018-2023 - Community Health and Social Services Network (CHSSN) (2018)
Keywords: Official Language Minority Community (OLMC)

L'initiative d'adaptation : guide des projets 2018-2023 - Community Health and Social Services Network (CHSSN) (2018)
Keywords: Official Language Minority Community (OLMC)

Québec Health 101 Guide - Jeffery Hale Community Services; Community Wellness Centre; Voice of English-speaking Quebec (VEQ) (2018)
This guide and the accompanying presentation were developed with the intention of helping newcomers navigate the medical system here in Québec City with a little more ease and efficiency. This project was a joint effort between Jeffery Hale Community Services, the Community Wellness Centre and the Voice of English-speaking Québec. This document was inspired by the Valcartier Family Centre Health Guide.

Annual Report 2017-2018 : Leading the Way - Leading English Education and Resource Network (LEARN) (2018)

Society Pages - Morrin Centre (2018)
Number of pages: 20

Society Pages - Morrin Centre (2018)
Number of pages: 24

Society Pages - Morrin Centre (2018)
Number of pages: 24

Society Pages - Morrin Centre (2018)
Number of pages: 32

Annual Report 2017-2018 - Voice of English-speaking Quebec (VEQ) (2018)

Travellin' Toddler Time : 2018-2019 Schedule - Voice of English-speaking Quebec (VEQ) (2018)